نموذج تعلم الخط في نهضة الخطاطين معهد دار القرآن والحديث المجيدية الشافعية نهضة الوطن الدنية الإسلامية فنشور - Muhammad Ul Azim; Ruwaida; Moh Nasikin; Lalu Ahmad Busyairi; Erma Suriani; Moh Riadhi (El-Tsaqafah : Jurnal Jurusan PBA, 2026)
This study aims to determine the "Calligraphy Learning Model at Nahdlatul Khattatin MDQH NWDI Pancor." The research objectives are to determine the learning model used in teaching calligraphy at Nahdlatul Khattatin and to identify the supporting and inhibiting factors in implementing the learning model at Nahdlatul Khattatin MDQH NWDI Pancor. The research methodology used in this study includes: 1) The type of research is qualitative; 2) The subjects of this study are calligraphy teachers and students at Nahdlatul Khattatin MDQH NWDI Pancor; 3) Data collection uses observation, interviews, and documentation techniques. 4) Analysis uses qualitative descriptive analysis techniques. The results of this study indicate that using an appropriate calligraphy learning model can make learning Quranic calligraphy effective and efficient, enabling students to easily understand and comprehend how to write calligraphy, as taught in class using the learning models used at Nahdlatul Khattatin MDQH NWDI Pancor